Modified everting sutures: an alternative treatment for mild to moderate epiblepharon. Issue 11 (17th April 2018) - Young, Stephanie M; Kim, Yoon-Duck; Woo, Kyung In
Abstract : Purpose: To describe a modified everting suture procedure which can be used in patients with mild to moderate epiblepharon who are undergoing general anaesthesia for surgical correction of coexisting ophthalmic conditions. Methods: A prospective, interventional, non-comparative case series on patients with mild to moderate epiblepharon who underwent the modified everting suture procedure using permanent nylon sutures while under general anaesthesia for other ophthalmic surgery, from May 2014 to May 2016, in a single tertiary institution. Main outcome measures were correction of epiblepharon, recurrence rate and complications. Results: There were a total of 29 patients. Mean age was 5.7±4.1 years (range 1.5–20 years). Twenty (69.0%) were male, 31.0% were female. All had concomitant surgery under general anaesthesia for levator resection (75.9%), frontalis sling (17.2%), strabismus surgery (3.4%) and coloboma correction (3.4%). Mean follow-up was 18.1±9.1 months. All patients were well corrected at 1 and 6 months postoperative follow-up. At 1 year after surgery, 28 (96.6%) were well corrected while one patient (3.4%) was undercorrected. At last follow-up, the overall recurrence rate was 6.9%, with a mean time from surgery to recurrence of 20.5 months. There were no complications encountered. Conclusions: The modified everting suture procedure is a safe, effective, quick and relatively easy procedure for selected patients with mild to moderate epiblepharon, who are undergoing general anaesthesia for surgical correction of their coexisting ophthalmic conditions.